Targeting Interleukin(IL)-30/IL-27p28 signaling in cancer stem-like cells and host environment synergistically inhibits prostate cancer growth and improves survival. Issue 1 (31st July 2019) - Sorrentino, Carlo; Yin, Zhinan; Ciummo, Stefania; Lanuti, Paola; Lu, Li-Fan; Marchisio, Marco; Bellone, Matteo; Di Carlo, Emma
Abstract : Background: Interleukin(IL)-30/IL-27p28 production by Prostate Cancer (PC) Stem-Like Cells (SLCs) has proven, in murine models, to be critical to tumor onset and progression. In PC patients, IL-30 expression by leukocytes infiltrating PC and draining lymph nodes correlates with advanced disease grade and stage. Here, we set out to dissect the role of host immune cell-derived IL-30 in PC growth and patient outcome. Methods: PC-SLCs were implanted in wild type (WT) and IL-30 conditional knockout (IL-30KO) mice. Histopathological and cytofluorimetric analyses of murine tumors and lymphoid tissues prompted analyses of patients' PC samples and follow-ups. Results: Implantation of PC-SLCs in IL-30KO mice, gave rise to slow growing tumors characterized by apoptotic events associated with CD4 + T lymphocyte infiltrates and lack of CD4 + Foxp3 + T regulatory cells (Tregs). IL-30 knockdown in PC-SLCs reduced cancer cell proliferation, vascularization and intra-tumoral Indoleamine 2, 3-Dioxygenase (IDO) + CD11b + Gr-1 + myeloid-derived cells (MDCs) and led to a significant delay in tumor growth and increase in survival. IL-30-silenced tumors developed in IL-30KO mice, IL-30 −/− tumors, lacked vascular supply and displayed frequent apoptotic cancer cells entrapped by perforin + TRAIL + CD3 + Tlymphocytes, most of which had a CD4 + T phenotype, whereas IL-10 + TGFβ + Foxp3 + Tregs were lacking. IL-30 silencing in PC-SLCs prevented lung metastasis in 73% of tumor-bearing WT mice and up to 80% in tumor-bearing IL-30KO mice. In patients with high-grade and locally advanced PC, those with IL-30 −/− tumors, showed distinct intra-tumoral cytotoxic granule-associated RNA binding protein (TIA-1) + CD4 + Tlymphocyte infiltrate, rare Foxp3 + Tregs and a lower biochemical recurrence rate compared to patients with IL-30 +/+ tumors in which IL-30 is expressed in both tumor cells and infiltrating leukocytes. Conclusion: The lack of host leukocyte-derived IL-30 inhibits Tregs expansion, promotes intra-tumoral infiltration of CD4 + T lymphocytes and cancer cell apoptosis. Concomitant lack of MDC influx, obtained by IL-30 silencing in PC-SLCs, boosts cytotoxic T lymphocyte activation and cancer cell apoptosis resulting in a synergistic tumor suppression with the prospective benefit of better survival for patients with advanced disease.